Holocene Rupture History of the Central Teton Fault at Leigh Lake, Grand Teton National Park, WyomingABSTRACT - Zellman, Mark S.; DuRoss, Christopher B.; Thackray, Glenn D.; Personius, Stephen F.; Reitman, Nadine G.; Mahan, Shannon A.; Brossy, Cooper C. (Bulletin of the Seismological Society of America, 2020)
Prominent scarps on Pinedale glacial surfaces along the eastern base of the Teton Range confirm latest Pleistocene to Holocene surface‐faulting earthquakes on the Teton fault, but the timing of these events is only broadly constrained by a single previous paleoseismic study. We excavated two trenches at the Leigh Lake site near the center of the Teton fault to address open questions about earthquake timing and rupture length. Structural and stratigraphic evidence indicates two surface‐faulting earthquakes at the site that postdate deglacial sediments dated by radiocarbon and optically stimulated luminescence to ∼10–11  ka⁠. Earthquake LL2 occurred at ∼10.0  ka (9.7–10.4 ka; 95% confidence range) and LL1 at ∼5.9  ka (4.8–7.1 ka; 95%). LL2 predates an earthquake at ∼8  ka identified in the previous paleoseismic investigation at Granite Canyon. LL1 corresponds to the most recent Granite Canyon earthquake at ∼4.7–7.9  ka (95% confidence range). Our results are consistent with the previously documented long‐elapsed time since the most recent Teton fault rupture and expand the fault’s earthquake history into the early Holocen